Sustainability in Social Enterprise Research: A Systematic Literature Review. (September 2022) - Jayawardhana, Kumudu; Fernando, Imali; Siyambalapitiya, Janaka
Given the noteworthy contribution to the global socio-economic development, research on social enterprises (SE) has gained prominence over past two decades. Making a clear departure from for-profit counterparts, the core purpose of SEs is to deliver a social mission while at the same time staying financially viable and as a consequence, "sustainability" is strongly embedded in their core drive of existence. Rapidly sprouting body of literature on SE posits that "sustainability" is intensely coincided with "social enterprises." Although "sustainability" has been a buzz word in the context of SE, lacking of systematization and categorization of knowledge hinders the advancement of SE specific research. Consequently, the primary objective of this paper is systematization and categorization of the extant knowledge on sustainability in SE research context. The study carried-out a systematic literature survey from reputed databases; Scopus, Social Science Citation Index and Science Direct. Removing the repetitions, 136 papers on sustainability was compiled for analysis. The analytical approach was two-fold: First, a citation analysis was performed in order to evaluate the prominent, emerging and popular sustainability-based research areas in the extant body of knowledge in the field. Second, a thematic analysis was performed to analyze and interpret explicit themes on which sustainability concept has been investigated. Paper discovered six themes that the sustainability concept has been researched through significant research popularity disparities can be witnessed among the discovered themes. Since this paper identifies several research gaps and inconsistencies, it noticeably sets path for future research on the concept of sustainability in SE.